2 cos 3 θ − cos θ sin θ − 2 sin 3 θ equals
This problem is part of the set Trigonometry .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sin q (1 - 2 Sin^2 q)/ [Cos q (2 Cos^2 q - 1)] = Sin q/ Cos q = Tan q
Either knowing Cos 2 q or
1 - 2 Sin^2 q = 1 - 2 (1 - Cos^2 q) = 2 Cos^2 q - 1
We common the factors s i n θ and c o s θ in Numerator and denominator respectively ,i.e.
c o s θ ( 2 cos 2 θ − 1 ) s i n θ ( 1 − s i n 2 θ ) = c o s θ ( 2 cos 2 θ − 1 ) s i n θ ( 2 cos 2 θ − 1 ) = c o s θ s i n θ = t a n θ
can you further explain why 1 - sin^2 theta = 2 cos^2 theta - 1
Problem Loading...
Note Loading...
Set Loading...
First, factor out tan θ to get tan θ 2 cos 2 θ − 1 1 − 2 sin 2 θ Next, use the identity sin 2 θ + cos 2 θ = 1 to get tan θ 1 − 2 sin 2 θ 1 − 2 sin 2 θ = tan θ